Application of the TOPSIS Method for Multi-Objective Optimization of a Two-Stage Helical Gearbox - Tran, Huu-Danh; Dinh, Van-Thanh; Vu, Duc-Binh; Vu, Duong; Luu, Anh-Tung; Vu, Ngoc Pi (Engineering, Technology & Applied Science Research, 2024)
In order to design a high-efficiency two-stage gearbox to reduce power loss and conserve energy, a Multi-Criterion Decision-Making (MCDM) method is selected for solving the Multi-Objective Optimization Problem (MOOP) in this research. The study’s objective is to determine the best primary design factors that will increase gearbox efficiency and decrease gearbox mass. To that end, the first stage’s gear ratio and the first and second stages’ Coefficients of Wheel Face Width (CWFW) were chosen as the three main design elements. Furthermore, two distinct goals were analyzed: the lowest gearbox mass and the highest gearbox efficiency. Additionally, the MOOP is carried out in two steps: phase 1 solves the Single-Objective Optimization Problem (SOOP) to close the gap between variable levels, and phase 2 solves the MOOP to determine the optimal primary design factors. Furthermore, the TOPSIS approach was selected to address the MOOP. For the first time, an MCDM technique is used to solve the MOOP of a two-stage helical gearbox considering the power losses during idle motion. When designing the gearbox, the optimal values for three crucial design parameters were ascertained according to the study’s results.